Clinical Measures for the Cytokine Levels After and Before Hirudotherapy in Rheumatoid Arthritis Patients - Dina A. A. AL-Roubaey (Journal of Global Pharma Technology, 2018)
Hirudotherapy is one of the oldest complementary medical methods using in treatment of disease like inflammatory disease, osteoarthritis, and after being surgery. The aim of this study was to identify what areroles of leech bioactive substances on the treating of rheumatoid arthritis disease. The study was carried out in Al-Najaf City/ Center of leech therapy, during the period from October 2016 to October 2017, the study involved (140) RA patients who attended the hospital, the majority of the study were women (64.29%), and the most effected age groups were from 61-70 years old in percentage (42.86%) followed by the age group 71-80 years old (25%), also the results showed a highly significant increased mean serum level of  hs-CRP  (9.35  vs. 1.19 mg/ ml), and cytokines including IL1β (59.87 vs.12.43 pg/ml), IL-6 (70.34vs. 13.33 pg/ml), IL-8 (53.25 vs. 11.61 pg /ml), IL-10(44.58 vs. 10.50 pg/ml), IL-17(77.45 vs. 10.42 pg/ml), and TNF-α(68.30 vs. 11.81 pg/ml) for RA patients as compared to controls group, in addition the study showed that the patients after hirudotherapy have a significant decreased mean serum level of  hs-CRP  and cytokines (IL1β, IL-6, IL-8, IL-10, IL-17, and TNF-α) as compared to the patients before hirudotherapy. It was concluded that leech therapy is a highly effective in treating RA patients by reducing the severity of disease. It was recommended to achieve more investigation for assassement the role of leech therapy and their bioactive substances in the treatment of RA disease.Keywords: Hirudotherapy, Cytokines, Rheumatoid Arthritis patients.